Uncertainty avoidance level and purchase intention in Hungarian e-commerce - Phamthi, Vananh (Marketing & Menedzsment, 2024)
THE AIM OF THE PAPER The study investigates the impact of individuals’ uncertainty avoidance level on the relationship between risk and purchase intention in Hungarian e-commerce. It also distinguishes between perceived risk and affective risk in the decision-making journey. METHODOLOGY The study conducts empirical research using a sample of 283 Hungarian online shoppers and applying structural equation modelling (SEM). MOST IMPORTANT RESULTS The findings show that perceived risk and affective risk negatively impact consumers' purchase intentions in Hungarian e-commerce. Further, uncertainty avoidance negatively moderates the relationship between perceived risk and purchase intention. The study emphasises the role of affective risk in the decision-making journey. It also supports investigating cultural differences at an individual level in the literature on perceived risk in e-commerce. RECOMMENDATIONS This study suggests that companies may improve Hungarian consumers’ perceptions regarding the seller's reliability, product quality, logistics capacity, etc. to diminish perceived risk and affective risk. Further, it reveals another approach to customer segmentation based on individual cultural values.